Determinants of Firm Value in Indonesia’s Property and Real Estate Sector - Muhamad Rafly Alifadi; Fanji Farman (E-Jurnal Akuntansi, 2026)
This study examines the effects of profitability, liquidity, and leverage on firm value in property and real estate companies listed on the Indonesia Stock Exchange during 2020–2024. The study used panel data from 204 observations and applied panel regression analysis with the Fixed Effect Model. The findings show that the model significantly explains firm value variation with an Adjusted R² of 0.902 and Sig. F of 0.000. Liquidity (CR) has a positive and significant effect on firm value, while profitability (ROA) and leverage (DER) have positive but insignificant effects. Firm size (SIZE), used as a control variable, negatively affects firm value. These findings indicate that liquidity is the main determinant of firm value in the property and real estate sector. The study implies that investors tend to prioritize financial stability and liquidity in assessing firm value.